Light supply to 'fuji' apple trees covered with hail protection nets and its effects on photosynthesys, yield and fruit quality Disponibilidade de luz em macieiras 'fuji' cobertas com telas antigranizo e seus efeitos sobre a fotossíntese, o rendimento e a qualidade dos frutos - do Amarante C.V.T.* (2009)
In apple orchards, hail damage can be avoided by covering the plants with nets. However, the nets might change light intensity and quality supplied to the plants and, therefore, affect yield and quality of the fruit. This research was carried out to assess these aspects on 'Fuji' apples trees uncovered and covered with white and black nets. The black net caused more substantial reduction of photosynthetic photons flux density (PPFD) available to the plants during the day (24.8%) than the white one (21.2%). The inner part of plants canopy covered by nets, especially under black net, received light with a lower red:far red ratio (R:FR), in comparison to uncovered plants. Only under black net, the reductions of PPFD and R:FR of the light supplied to the plants increased the mean area and the specific area of the leaves and reduced the potential photosynthesis, leading to a reduction of yield (number and weight of fruits per cm-2 of trunk cross section area) and the red color of the fruit. The white and black hail protection nets reduced the incidence of sunburn but had no effect on russeting severity and number of seeds/fruit.